P1243 Nonbacterial thrombotic endocarditis (NBTE) of the aortic valve: incidental finding in hospitalized patients with advanced heart failure. (17th January 2020) - Marin, G G; Margineanu, C; Penes, D; Maresiu, C; Boiangiu, S; Stoica, E; Radu, R; Antohi, E L; Chioncel, O
Abstract: Background: The presence of small mobile masses on the ventricular side of the aortic valves in the absence of valvular regurgitation and signs of systemic inflammation has been previously described as marantic endocarditis and is now referred to as nonbacterial thrombotic endocarditis (NBTE). It is thought to be associated with endothelial dysfunction and procoagulative status, as is the case of acute decompensated heart failure (HF). Case description: We present a series of three male patients, with similar clinical characteristics, who were admitted for acute decompensated HF. All three patients had chronic HF, due to non-ischemic dilated cardiomyopathy with severe biventricular dysfunction, with resynchronization therapy, with elevated natriuretic peptides and previous HF hospitalizations in the past year requiring prolonged intravenous treatments. Other clinical, biological criteria for the definition of advanced HF were also met. All patients were under chronic anticoagulation treatment using a direct oral anticoagulant because of persistent atrial fibrillation. Thorough echocardiographic evaluation (both transthoracic and transoesophageal ultrasound) identified small mobile masses on the ventricular side of the aortic valves, centrally, on the line of cusp coaptation, with only minor central regurgitation. The lack of progression of valve lesion and the absence of gross signs of inflammation (no fever, normal hemoleucogram, normal CRP, repeated negative blood cultures) on serial examinations during several weeks follow-up allowed for the exclusion of infective endocarditis. In one case we also identified a left atrial appendage thrombus and presumably thrombotic masses attached to right side pacing leads. No clinically systemic embolic events were identified. Conclusion: We consider this to be an incidental finding in the given subclinical prothrombotic and inflammatory predisposing milieu of advanced chronic HF and the increasing high quality echocardiography imaging. Its clinical significance is still unknown, while differential diagnosis from subacute or chronic endocarditis relies largely on clinical judgment.